Implementation Of Minimum Service Standards For Patients For National Health Insurance Participants In Outpatient Units Pratama Clinic Inpatient Care Siti Khodijah, Blitar City - Amarin Yudhana; Tri Wahyuni R (Universitas STRADA Indonesia, 2022)
The implementation of SPM in the health sector cannot be separated from the implementation of the National Health Insurance program (JKN) or the Social Security Agency (BPJS) because of the complementary and synergistic nature. Patient satisfaction in accordance with the minimum service standards is an indicator of the standard of a hospital/health clinic/health care facilities and a measure of service quality. Low satisfaction will affect the number of visits in the hospital, while the attitude of employees towards patients will also have an impact on patient satisfaction where the needs of patients from time to time will increase, as well as the demands on the quality of services provided.Services provided to pregnant women in accordance with Permemkes number 4 of 2019 at least four times during pregnancy with a schedule of one time in the first trimester, one time in the second trimester and two times in the third trimester carried out by midwives and or doctors and or midwifery specialists both working in public and private health service facilities that have a registration certificate (STR). The study used a qualitative method with a narrative approach with Purposive Sampling with the background of the event caused by the experience of yourself and the experience of others as a form of knowledge about the health of the three informants of pregnant women. And there is a relationship of knowledge with the implementation of service standards according to permennkes number 4 of 2019. This means that the level of relationship between knowledge and implementation is quite sufficient with the suggestion that the primary clinic inpatient Siti Khodijah conduct training on Ante Natal Care services for health workers, especially midwives pregnant women to support the accuracy of the examination.